1997
DOI: 10.1016/s1010-7940(97)01218-9
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular remodelling and improvement in Freestyle stentless valve haemodynamics

Abstract: After stentless aortic valve replacement, LV mass index and wall thickness both fall towards normal, and myocardial stroke work increases. These ventricular remodelling processes are accompanied by a more physiological flow jet at valve cusp level, which permits a greater stroke volume to be ejected with a smaller transvavular velocity increase, so that effective orifice area increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These findings corroborate those previously noted by other investigators. 12,15,26,27,[31][32][33] When the data are tabulated according to valve size, the mean transvalvular gradient and EOA are similar to those reported for the Toronto SPV valve 15,26,27 but compare favorably to the Biocor 31 and Prima 13,16 stentless prostheses.…”
Section: Hemodynamicsmentioning
confidence: 63%
“…These findings corroborate those previously noted by other investigators. 12,15,26,27,[31][32][33] When the data are tabulated according to valve size, the mean transvalvular gradient and EOA are similar to those reported for the Toronto SPV valve 15,26,27 but compare favorably to the Biocor 31 and Prima 13,16 stentless prostheses.…”
Section: Hemodynamicsmentioning
confidence: 63%
“…Some investigators have reported a negligible pressure drop and nearly perfect relief of LVH after stentless xenograft valve implantation [20,21]. However, investigations on blood pressure were omitted in those papers and no wide consensus exists on this matter at present [22].…”
Section: Discussionmentioning
confidence: 99%
“…An early reduction in hypertrophy thus seemed to lead to superior ventricular function, and may result in a better prognosis for the patient. 1,6 In our experience, however, there was one patient who had a residual peak pressure gradient of more than 30 mmHg after implantation of a 21 mm Freestyle" bioprosthesis using a root inclusion technique, Her body surface area was 1.56 m-, which was larger than 2 other patients (1.21 m 1 and 1.40 m') who had the same size of bioprosthesis implanted with no significant residual transvalvular gradient. It seems that a full root technique was preferable in this case because it allowed for a larger size of bioprosthesis than the other implantation techniques, We used this bioprosthesis for two patients with active endocarditis.…”
Section: Discussionmentioning
confidence: 66%